FRI0451 Continuous presence of igm anti-topoisomerase i antibodies indicates an ongoing immune response in systemic sclerosis. (12th June 2018) - Boonstra, M.; Bakker, J.A.; Grummels, A.; Ninaber, M.K.; Ajmone Marsan, N.; Scherer, H.U.; Toes, R.E.; Huizinga, T.W.; de Vries-Bouwstra, J.K.
Abstract : Background: Small case-series of anti-topoisomerase I antibodies (ATA) in Systemic Sclerosis (SSc) show a highly varying immune response over time. IgA and IgG levels were shown to correlate with skin scores. One small study showed that increasing IgG levels can precede increasing skin scores. Thus far, detailed analysis of ATA characteristics with disease features in larger cohorts have not been performed. Objectives: By taking advantage of our well described SSc cohort with annual follow-up data, we aimed to evaluate whether clinical heterogeneity within ATA +patients can be explained by ATA characteristics. Methods: ATA IgG, IgM and IgA levels were assessed in consecutive serum samples of baseline ATA-IgG +patients from the Leiden SSc cohort. Disease progression during the first year of follow-up was defined as increase of modified Rodnan Skin Score (mRSS) with ≥5 points, progression of pulmonary involvement (-≤10% of predicted forced vital capacity [FVC] or diffusion capacity of the lung [DLCO]), development of digital ulcers, renal crisis, pulmonary arterial hypertension and/or mortality. Here, we present data on the association between the presence of ATA-IgM and disease progression. Results: In total 344 samples of 102 ATA +patients were measured. Baseline and follow-up samples were available from 70 patients. Median follow-up was 3.7 years (range 0.9–7.4 years). At baseline 42/70 patients were positive for ATA IgM and 69/70 patients for ATA IgA (table 1). Strikingly, while clinical characteristics did not differ, mean ATA-IgM at baseline was higher in disease progressors (table 2). The possible relevance of an ATA-IgM response for disease progression was confirmed by the observation that of those patients positive for ATA-IgM both at baseline and at FU, 59% of cases showed disease progression, as compared to 15% of patients negative for ATA IgM at both time points (p=0.02). Conclusions: The presence of ATA-IgM at baseline and at follow-up and its association with disease course suggests that the ATA response in SSc patients is an ongoing process that possibly explains the heterogenic disease course of ATA +patients over time. Disclosure of Interest: None declared